The smartest kid in the universe (Smartest kid in the universe, 1,, 2020)
When seventh-grader Jake McQuade mistakes the world's first ingestible knowledge pills for jelly beans, he suddenly knows all about physics and geometry and can speak Swahili (though Spanish would be a lot more useful)--but his sort-of girlfriend Grace thinks they can use his new found brilliance to save their middle school from the new principal, who is conspiring to get it shut down.